Analysis of amendments to government regulation no 57 concerning national education number 04 of 2022 - Syahidan, Ade Iman; Rahmat, Pupu Saeful (Institute of Computer Science (IOCS), 2023)
Education is one of the important sectors in the development of a country. Indonesian education is faced with various challenges, both internal and external challenges. Indonesian Government Regulation (PP) Number 57 of 2021 concerning National Education being changes policy Number 4 of 2022. This changes cause uncertainty legally and administratively in formal carry out educational activities. Several important changes have been noted in PP 57 of 2021 concerning National Education period 4 of 2022. These changes include curriculum adjustments, building an assessment system, increasing the quality of the number of teachers and teaching staff and changes in education management at the school National level. With the issue arise, there is need for analyze the changes made in PP 57 of 2021 and their impact on national education system. This research aim to investigates the impact of implementation new regulation policy Number 4 of 2022. The method used is literature study. The results show that there’s have been significant changes in PP 57 of 2021 which affect various positive aspects of national education system. Adjusting the curriculum, improving the quality of teachers, and developing evaluations are important steps in improving the quality of education in Indonesia.